The impact of inequality: how to make sick societies healthier - Wilkinson, Richard G. (London, 2005)
"Why does the United States, the richest country in the world, rank twenty-fifth in international life expectancy? Pioneering epidemiologist Richard Wilkinson demonstrates that inequality is socially corrosive and affects health because the quality of social relations is crucial to well-being. The poor health performance of the United States, its high rates of violence, and its low social capital all reflect how societal relations are strained to the breaking point by record levels of inequality. In wealthy countries, health is not simply a matter of how material circumstances determine your quality of life and access to health care; it is how your social standing makes you feel. The Impact of Inequality explains why low social status -being devalued and looked down on- is so stressful and can have devastating effects on people's lives and communities. Comparing the United States with other market democracies and one state with another, this book shows why more unequal societies have poorer communal environments, and why the whole social spectrum suffers everything from higher levels of violence to more widespread depression. The Impact of Inequality presents a radical theory of the psychosocial impact of class stratification, with particular emphasis on health and the quality of societal relations. It addresses people's experience of class and inequality and the pervasive sense that modern societies, despite material success, are social failures. At the same time, it shows that even small reductions in inequality matter, compelling us to pursue greater social and political equality to improve life for everyone. "